Education Based-Application And Prenatal Yoga Reduces Cesarean Section - Ni Made Dewianti; Kadek Widiantari; Ni Nyoman Deni Witari; Made Pradnyawati Chania (Jurnal MID-Z (MIDWIFERI ZIGOT), 2023)
The incidence of cesarean section (CS) continues to increase from year to year, pregnant women choose cesarean Section not because there are medical indications but because of fear of normal delivery. Interventions are needed to reduce the incidence of CS. A quasi-experimental design with a pre-post control group design was used, the sample used was pregnant women in the second trimester with a gestational age of 18-20 weeks with a sample distribution of 30 intervention groups and 30 control groups, using paired t-test, independent t-test and Chi-square. In the intervention group and control group, the highest percentage for the characteristics of respondents, age 20-35 years, higher education, work and the majority ethnicity in this study is Balinese, there is a significant difference in knowledge between the intervention group and the control group with a value (p = 0.000), there is a significant difference in attitude between the intervention group and the control group with a value (p = 0.000) and the intervention can reduce the incidence of CS by 37.6% with a value of p = 0.001. Interventions with education based-application and prenatal yoga can increase knowledge,and attitudes are effective in reducing the incidence of CS.